2011
DOI: 10.3415/vcot-11-04-0061
|View full text |Cite
|
Sign up to set email alerts
|

Single cycle to failure in bending of three standard and five locking plates and plate constructs

Abstract: Due to differing plate construct properties inherent to these diverse implant systems, identical approaches to fracture management and plate application cannot be applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
88
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 40 publications
(43 reference statements)
3
88
0
1
Order By: Relevance
“…We showed that in a fracture gap model with cadaveric canine bone, the SOP had significantly greater properties in 4‐point bending in static and cyclic testing than the LCP. Our results seem to correlate with the mechanical qualities of the plate itself as previously reported . The SOP plate is anticipated to react in this manner given its greater section modulus compared with the LCP plate but the finding that it is still superior to the LCP when tested on a cadaveric bone construct suggest that in a clinical setting the SOP might be more adequate at resisting bending forces than an LCP system.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We showed that in a fracture gap model with cadaveric canine bone, the SOP had significantly greater properties in 4‐point bending in static and cyclic testing than the LCP. Our results seem to correlate with the mechanical qualities of the plate itself as previously reported . The SOP plate is anticipated to react in this manner given its greater section modulus compared with the LCP plate but the finding that it is still superior to the LCP when tested on a cadaveric bone construct suggest that in a clinical setting the SOP might be more adequate at resisting bending forces than an LCP system.…”
Section: Discussionsupporting
confidence: 86%
“…The LCP requires specialized locking head screws in order to be used as a locking system but has combination holes that can accommodate both conventional and locking screws. The mechanical properties of the SOP and LCP have already been tested against other commonly used locking and non‐locking plates . The SOP has shown greater bending stiffness, bending structural stiffness and bending strength than comparable plates in vitro …”
mentioning
confidence: 99%
“…Other important factors necessary for valid results are model geometry, and appropriate definition of the material properties and boundary conditions. To date, biomechanical studies conducted on animals and cadavers have been taken as reference when evaluating the reliability of different fixation materials and designs for fracture fixation (4,5). Therefore, more widespread use of FEM in biomedical studies would lead to savings in time and resources, thereby promoting the success of orthopedic trauma surgery and expanding horizons.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the main problem in plate-screw fixation is the loosening and/or fracture that are formed due to the load on the plate and screw (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Today, main problems in plate-screw fixation are the loosening and/or fracture that are formed due to the load on the plate and screw (1,2). Even though early problems related with plate-screw such as metal corrosion and resistance failures have now been corrected, it cannot be stated that more recent designs have solved all problems.…”
Section: Introductionmentioning
confidence: 99%